2012
DOI: 10.1590/s0004-28032012000400010
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with 0.1% and 2% vitamin e in diabetic rats: analysis of myenteric neurons immunostained for myosin-V and nNOS in the jejunum

Abstract: -Context -Diabetes mellitus is a disease characterized by hyperglycemia that, when allowed to progress long-term untreated, develops vascular and neurological complications, which are responsible for the development of alterations in the enteric nervous system in diabetic patients. In the gastrointestinal tract, diabetes mellitus promotes motor and sensory changes, and in the reflex function of this system, causing gastroparesis, diarrhea, constipation, megacolon, slow gastrointestinal transit, gastric stasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…[ 48 ] reported that the myenteric plexus regulates mucosal cell proliferation in an inhibitory manner. Loss of myenteric neurons [ 49 ] and enhanced cell body area [ 50 ] of submucous neurons are reported in the literature, and can be associated with reduction of the total number of neurons in diabetes. Tronchini et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 48 ] reported that the myenteric plexus regulates mucosal cell proliferation in an inhibitory manner. Loss of myenteric neurons [ 49 ] and enhanced cell body area [ 50 ] of submucous neurons are reported in the literature, and can be associated with reduction of the total number of neurons in diabetes. Tronchini et al .…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation with these vitamins alone also showed promising results with regard to enteral neuroprotection (Pereira et al 2006;Zanoni et al 2007;Pereira et al 2008;Roldi et al 2009;Zanoni et al 2009). However, other studies that tested the effects of these vitamins alone found that vitamin C ) and vitamin E (Tronchini et al 2012) did not preserve enteric neurons in diabetic rats. These results demonstrate that the combination of these antioxidants may more markedly reduce oxidative stress and thus reduce the deleterious effects of diabetes.…”
Section: Discussionmentioning
confidence: 94%
“…Some studies have shown that both EGCs and enteric neurons are affected by diabetes [11,13,14]. Many studies have sought to verify the action of antioxidants (e.g., quercetin, vitamin E, vitamin C, L-glutamine, and L-glutathione) in diabetic neuropathies [14][15][16][17][18]. The present study evaluated the effects of an ethyl-acetate fraction (EAF) from Trichilia catigua, which has been reported to exert better antioxidant effects than the crude extract [19].…”
Section: Introductionmentioning
confidence: 99%